Assessment and Feedback in Higher Education: A Meta-analysis of Best Practices and Student Perceptions - Meisuri Meisuri (Penelitian dan Pengembangan Ilmu, 2024)
Assessment and feedback in higher education play a key role in improving students' learning experiences and academic outcomes, especially in online and hybrid learning contexts. This research aims to explore students' perceptions of the effectiveness of various assessment and feedback methods in this environment. The method used is systematic meta-analysis with the PRISMA approach, involving collection and analysis of data from various international databases. The results showed that immediate and delayed feedback had different impacts on learning, with immediate feedback supporting rapid error correction and delayed feedback improving knowledge retention. The implication of these findings is the need to design assessment strategies that consider feedback timing and effective integration of online elements in hybrid learning to increase student motivation and learning outcomes.